Why brilliant people believe nonsense : a practical text for critical and creative thinking - Miller, Cherie K. (Acworth, GA Wisdom Creek Academic, 2015)
The passing of time reveals much expert opinion to be nonsense. How can we evaluate expert opinion and learn to think for ourselves? "In the midst of an information explosion, we face a wisdom deficit," notes author J. Steve Miller. This book, in a remarkably accessible and entertaining way, equips readers to think more clearly, innovate more creatively, see through the deceptions of clever advertisers and salesmen, simplify complex and convoluted arguments, manage life's decisions with more confidence, and express convictions more powerfully. This book is designed to be read by all individuals interested in learning critical and creative thinking skills. It can also be used as a text targeting high school seniors and college freshmen. An accompanying website offers free lesson plans and teaching tips.
Includes bibliographical references and index.
Keywords: Critical thinking; Creative thinking